The effectiveness of competitive activity of highly qualified basketball players is influenced by the indicators characterizing speed and strength qualities during jumps - Losin B.E. ,; Grigorieva D.V. ,; Minina L.N. ,; Sergazinova M.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. Within the framework of this study, the task was to establish the relationship between the speed of performing jumping movements and the success of competitive activity of professional basketball players. Methods and structure of the study. 17 qualified basketball players took part in the scientific work. The components of the players' jump speed (reaction speed when performing a jump, the time of the motor phase of the jump, the speed of jumping, etc.) were determined based on the use of a dynamoplatform with an automated TABS system (Simulator Analyzer of Speed and Strength). The game indicators were calculated according to the statistical protocols of the games. Results and conclusions. The effectiveness of competitive activities in modern basketball is influenced by various indicators of players' fitness. The most important of them is the speed of the jump. The study revealed a statistically significant effect of the speed of the jump on such game parameters of basketball players as the points scored in the game, the number of rebounds of the ball under the ring and the utility coefficient of the player. The survey revealed the opinion of the coaches about the importance of controlling the level of jump speed in the process of training basketball players. At the same time, almost half of the respondents noted that they experience serious difficulties in assessing this indicator. In this situation, it is necessary to search for simple tests and their scientific justification to assess the speed of basketball players' jumps.